2004
DOI: 10.1152/ajpheart.00742.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium and superoxide dismutase in sensitizing mitochondria to peroxynitrite-induced permeability transition

Abstract: The mitochondrial permeability transition pore (PTP) is a membrane protein complex assembled and opened in response to Ca(2+) and oxidants such as peroxynitrite (ONOO(-)). Opening the PTP is mechanistically linked to the release of cytochrome c, which participates in downstream apoptotic signaling. However, the molecular basis of the synergistic interactions between oxidants and Ca(2+) in promoting the PTP are poorly understood and are addressed in the present study. In isolated rat liver mitochondria, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…NO is known to affect mitochondrial respiration as well, except at the level of cytochrome c oxidase (complex IV), and this decreases O 2 consumption without affecting ATP synthesis (Brookes et al, 2002). The short-term effect of SIN-1, but not NONOates, on ATP levels is also consistent with the idea of differential effects of NO and ONOO Ϫ on mitochondrial permeability transition and calcium handling, both processes which can contribute to cell death (Horn et al, 2002;Brookes and Darley-Usmar, 2004). Again, the effect of NO is believed to be reversible, whereas that of ONOO Ϫ is not (Horn et al, 2002;Brookes and Darley-Usmar, 2004).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…NO is known to affect mitochondrial respiration as well, except at the level of cytochrome c oxidase (complex IV), and this decreases O 2 consumption without affecting ATP synthesis (Brookes et al, 2002). The short-term effect of SIN-1, but not NONOates, on ATP levels is also consistent with the idea of differential effects of NO and ONOO Ϫ on mitochondrial permeability transition and calcium handling, both processes which can contribute to cell death (Horn et al, 2002;Brookes and Darley-Usmar, 2004). Again, the effect of NO is believed to be reversible, whereas that of ONOO Ϫ is not (Horn et al, 2002;Brookes and Darley-Usmar, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…The short-term effect of SIN-1, but not NONOates, on ATP levels is also consistent with the idea of differential effects of NO and ONOO Ϫ on mitochondrial permeability transition and calcium handling, both processes which can contribute to cell death (Horn et al, 2002;Brookes and Darley-Usmar, 2004). Again, the effect of NO is believed to be reversible, whereas that of ONOO Ϫ is not (Horn et al, 2002;Brookes and Darley-Usmar, 2004). Nevertheless, Clementi et al (1998) have shown that persistent (Ͼ6 h) exposure of cells to NO can eventually lead to mitochondrial inhibition, possibly through complex I S-nitrosylation, and ATP depletion.…”
Section: Discussionsupporting
confidence: 81%
“…However, in addition to its induction of the intrinsic apoptotic pathway via alteration of upstream signaling events, peroxynitrite may directly alter mitochondrial function via oxidative damage, which has been reported using isolated mitochondria. 17 Such direct, deleterious effects of peroxynitrite on mitochondria may also be rescued by treatment with cyclosporin A. Regardless of the initiating event, our results indicate that the induction of the intrinsic apoptotic pathway by peroxynitrite is regulated by alterations in mitochondrial function ( Figure 9).…”
Section: Discussionmentioning
confidence: 61%
“…5,[7][8][9] When peroxynitrite is directly added to preparations of isolated mitochondria, the permeability transition pore is activated and cytochrome c is released, suggesting that peroxynitrite-induced apoptosis may be the result of direct oxidative damage to the mitochondria. 17 However, other studies have shown that peroxynitrite-induced apoptosis could be either inhibited or enhanced by treatment with trophic factors, 5,6 suggesting a regulated process. In the current study, we report that peroxynitrite activation of the intrinsic or mitochondrial apoptotic pathway in PC12 cells is preceded by phosphorylation of p38 and JNK MAPK and by translocation of phosphorylated JNK to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that acute rejection occurs upstream of cardiomyocyte apoptosis and that inhibiting MPT opening may provide a mechanism to prevent actual graft failure. In addition to high Ca 2ϩ , reactive oxygen and peroxynitrite trigger MPT pore opening in liver mitochondria ex vivo (Brookes and Darley-Usmar, 2004). Based upon these findings, we cannot exclude the possibility that WW85 might provide cardiac protection by a mechanism involving inhibition of peroxynitrite-mediated MPT pore opening leading to diminished apoptosis.…”
mentioning
confidence: 90%